Tindak Komunikasi Verbal dan Nonverbal Bentuk Lepas Hormat dalam Bahasa Bali - I Nengah Suandi; Made Sri Indriani (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
This study aims at describing (1) quatitative appropriateness between verbal and nonverbal communicatin acts of Balinese speakers’ loosely respective forms and 2) qualitative appropriateness between verbal and nonverbal communication acts of Balinese speakers’ loosely respective forms in four villages in Bali. This appropriateness is viewed from the macro and micro linguistic functions. The subjects of this study were Balinese speakers (young generation, adult people, and old people from four villages in Bali. The data in the form of quantitative appropriateness were collected by means of questionnaire and observation with eliciting technique. The collected data were analyzed descriptively. The result of the study shows that with respect to Balinese speakers’ loosely respective forms of utterances (1) quantitatively, there was no appropriateness between verbal communication acts and nonverbal communication acts and (2) there was an appropriateness between verbal communication acts and nonverbal communication acts, in the sense that the presence of nonverbal communication acts was notparticularly intended to respect the interlocutors, but it was merely intended (1) to complete verbal messages (2) to clarify verbal messages, and (3) to emphasize verbal messages being delivered.